2013
DOI: 10.1091/mbc.e13-04-0223
|View full text |Cite
|
Sign up to set email alerts
|

Environmental cues induce a long noncoding RNA–dependent remodeling of the nucleolus

Abstract: Environmental signals, such heat shock and acidosis, induce a structural and functional remodeling of the nucleolus. This process, which depends on the expression of intergenic long noncoding RNA, reversibly converts the nucleolus from a transcriptionally active ribosome factory into a transcriptionally inert prison for proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
106
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(111 citation statements)
references
References 56 publications
(54 reference statements)
5
106
0
Order By: Relevance
“…Nevertheless, our results, which demonstrate an ATPdependent decrease in nucleolar diffusion (i.e., an increase in molecular crowding), are consistent with previous results on the relative increase in nucleolar viscosity due to ATP depletion (42). As suggested in previous studies, our results support the conclusion that an ATP-dependent or transcriptional change in the microenvironment is a common phenomenon associated with active molecular processes in nucleolar assembly (18,42,43).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, our results, which demonstrate an ATPdependent decrease in nucleolar diffusion (i.e., an increase in molecular crowding), are consistent with previous results on the relative increase in nucleolar viscosity due to ATP depletion (42). As suggested in previous studies, our results support the conclusion that an ATP-dependent or transcriptional change in the microenvironment is a common phenomenon associated with active molecular processes in nucleolar assembly (18,42,43).…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that the nucleolar microenvironment is relatively charged compared with that of chromatin and that this microenvironment makes the mobility of charged molecules markedly slower, even though further investigation will be required to quantitating the mobility change of charged inert molecules in heterochromatin, mitotic chromosomes, and nucleoli, respectively (20,37). Recent study demonstrated that cellular stress induced formation of a subnucleolar structure called detention center consisted of long noncoding RNA, and mobility of the detention center-related nucleolar proteins, which have various phosphosites and pI values, were immobilized (43). It will be interesting to examine various types of electrostatic charge sequences in the probe molecule with the same molecular size.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all five nuclear bodies with arcRNA scaffolds form or increase in size or number upon cellular stresses or in specific developmental and disease conditions (Table 1). For instance, upon heat shock, much transcription and RNA processing is shut down, partly due to the sequestration of nucleic acid-binding proteins into nuclear bodies [34,41,42]. When such stresses are no longer present, arcRNAs can be quickly degraded and proteins trapped in stress-inducible nuclear bodies disperse into the nucleoplasm, rapidly allowing gene expression to return to normal.…”
Section: Figmentioning
confidence: 99%
“…Interestingly, the IGS lncRNA and its interacting proteins form a large subnucleolar structure named the detention center (DC), and the formation of the DC is dependent on the expression of IGS lncRNA (Jacob et al, 2013). A recent report has revealed that the maturation of pRNA, originated from the processing of an IGS lncRNA, is required for the establishment of heterochromatin at ribosomal RNA genes during ES cell differentiation (Savic et al, 2014).…”
Section: Prna and The Nucleolusmentioning
confidence: 99%